PENGARUH PERPUTARAN KAS, LDR, DAN CAR TERHADAP PROFITABILITAS PADA LPD DESA BONDALEM - Kartika Dewi, Putu Audhya Rahayu (E-Jurnal Manajemen; Vol 3 No 1 (2014), 2014)
ABSTRACT The purpose of this research is acknowledging the impact signification of cash turnover, LDR,and CAR as they go with profitability on penitentiary village of Bondalem. The research itself was based on case study. The amount of period which is used are 60 month. Multiple linear regression is used as the analytical technique. Based on the analyzing result it is discovered that cash turnover, LDR, and CAR are simultaneously effecting the profitability on a significant level, meanwhile partially cash turnover’s having positive impact on the profitability, LDR impacting negatively, whilst CAR some positive impact on smaller standards which is not significantly effecting the profitability. Keywords: Cash Turnover, LDR, CAR, Profitability.